Women, Education and Work in Italy: Don’t let your guard down! - Macale, Carlo (Formazione & insegnamento, 2025)
The paper is a social pedagogical study that aims to reflect on the issue of education/training and women's work in Italy. The issue raised still requires pedagogical commitment to ensure gender equality not only on an economic and social level, but above all on a cultural level. The study draws on recent research and monitoring which show that, despite the enactment of certain laws and the commitment of Italian politics to gender equality, the desired results have not been achieved. This implies a social pedagogical engagement to contrast stereotypes and discrimination, especially in the family, education and work contexts. In these contexts, social pedagogy will have to be influenced by reflections from gender pedagogy in order to eradicate certain implicit cultural prejudices.